ACCOUNTING OF INCOME AND EXPENSES: DOMESTIC AND FOREIGN EXPERIENCE - BENKO, Vitaliy (Scientific journal «World of Finance», 2024)
Introduction. The analysis of received income and spent expenses should be based on principles that ensure the proper organization of accounting in accordance with the applied classification of these important indicators, both in domestic and foreign practice. A well-established system facilitates the application of the correct grouping of activity indicators, establishes the relationship between them and provides an opportunity to justify the expediency of spending in the field of electronic communications. The purpose of the article is to analyze the features of activities in the field of electronic communications and their impact on the income and expense accounting system. Results. The results of the study provide an opportunity to identify and substantiate the correct choice of the proposed assortment policy, which creates convenient conditions for obtaining a variety of services, methods of providing them, other organizational and technological processes that cause an impact on the accounting system of income and expenses. Conclusions. It is well-founded that revenues in the field of electronic communications change under the influence of market demand, so it is necessary not only to study this market, but to forecast changes in it, which makes it possible to make informed management decisions in the future. Particular attention should be focused on the analysis of sales, changes in customer demand, competitors’ activities, use of the latest technologies, calculation problems, which contributes to further effective work.